Pyroelectric composite film for X-ray intensity detection - Sakamoto, Walter Katsumi [UNESP] (2012)
Composite material obtained with modified lead titanate (Pz34) ferroelectric ceramic and polyether-ether-ketone (PEEK) polymer matrix was used as sensitive component to measure X-ray intensity in a novel detection system. The sensing element works as a thermal transducer, converting a non-quantified thermal flux into an output measurable quantity of electrical voltage. The samples were obtained up to 60 vol.% of ceramic, by hot pressing the mixture of Pz34 and PEEK powders at 368 °C and applying 12 MPa pressure for 2.0 hours. The sensor response varies from 2.70 to 0.80 V in the energy fluence rate range of 6.30 to 37.20 W.m-2. The absorbed incident energy was analyzed as a function of the ionizing energy. Furthermore, by measuring the pyroelectric activity of the composite film it was observed that there is no degradation of the sensor after the irradiation.